Experimental Investigation of Water Cooler System by Using Eco-Friendly Refrigerant (R-134a) - Velkar, Rajendra B.; More, Nagesh S.; Dongare, Vaibhav K.; Mulgund, Anirudha G.; Gardi, Vaibhav V.; Surve, Dattatray D. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
With the recent government regulations, of banning the ozone depleting substances and Kyoto protocol later on curtaining to the use of substances which contribute to global warming, conventional refrigerants are to be replaced by the environment friendly refrigerants. Present day mankind depends heavily on refrigeration for his daily needs. This can be noticed by wide range of applications such as for home refrigeration, comfort cooling, preservation and transport, commercial and industrial air conditioning, hospitals, offices etc. These refrigeration system works on simple vapour compression refrigeration cycle. The water cooler system also works on simple vapour compression refrigeration cycle and uses R134a as a refrigerant. It is environment friendly. The performance of refrigerant R134a has been found and the results were used to evaluate the behavior of the system under varying load conditions and to measure the COP of the system. The water cooler system has been designed and fabricated specially for small capacity.